Contribution to the analysis of driver behavioral deviations leading to road crashes at work - Heddar Yamina; Djebabra Mébarek; Belkhiri Mohammed; Saaddi Saadia (IATSS Research, 2023)
Most road crashes at work are caused by Driver Behavioral Drift (DBD). This DBD has become a recurring issue on congested road sections.In this context, this study proposes a method called (MASOCU-DBD) which allows to analyze this DBD problem in two steps: assessment of the dynamics of DBD occurrence using a model called BM-NSA and analysis of DCC using a Cost-Benefit Analysis (CBA) weighted by the Analysis Hierarchical Process (AHP).The application of the MASOCU-DBD on a road section of an Algerian city's entry highlighted the problem of the DBD in terms of its occurrence and uselessness in the studied section.The merit of the proposed method is that it uses multi-criteria analysis tools (AHP and CBA) as well as a mathematical model (BM-NSA) to analyze professional drivers' behavioral deviations.